PENDEKATAN PERMAINAN TRADISIONAL UNTUK MENINGKATKAN HASIL BELAJAR PSIKOMOTORIK MERODA PADA SISWA KELAS VIII SMP NEGERI 2 SEMARANG - Ardha, Raditya; Kresnapati, Pandu; Juwahir, Juwahir (YLPK Mahardhika, 2025)
This study aims to analyze the implementation of a traditional games approach in floor gymnastics learning, specifically to improve the psychomotor learning outcomes of the cartwheel movement in eighth-grade students at SMP Negeri 2 Semarang. In this study, the traditional game of